2022
DOI: 10.3390/ijerph19052772
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Fruit and Vegetable Affordability on the Thrifty Food Plan Depends on Purchasing Power and Safety Net Supports

Abstract: The Supplemental Nutrition Assistance Program (SNAP) increases the food purchasing power of lower-income households so that they can better afford a nutritious diet. Benefit amounts are based in part on the cost for a household to follow the Thrifty Food Plan (TFP), a meal pattern designed to meet the Dietary Guidelines for Americans. In October 2021, the U.S. Department of Agriculture (USDA) reformulated the TFP and increased its cost by 21%. However, the TFP still does not account for differences in food pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Young and Stewart (2022) [ 63 ] examined the sufficiency of the TFP increase in SNAP benefits to afford FVs around the country. Importantly, TFP guidance is a standard estimate that does not account for variations in food prices across different U.S. geographies/contexts [ 60 ].…”
Section: Special Issue Contributions To Advancing Nutrition Security ...mentioning
confidence: 99%
See 3 more Smart Citations
“…Young and Stewart (2022) [ 63 ] examined the sufficiency of the TFP increase in SNAP benefits to afford FVs around the country. Importantly, TFP guidance is a standard estimate that does not account for variations in food prices across different U.S. geographies/contexts [ 60 ].…”
Section: Special Issue Contributions To Advancing Nutrition Security ...mentioning
confidence: 99%
“…While authors found, on average, increased SNAP benefits to be sufficient for households to meet DGA recommendations for FV purchases, affordability barriers by location were evident. Households residing in areas with higher than average food prices likely need to spend a larger percentage of their overall food budget on FVs to meet the DGA relative to households in areas with average or lower than average food prices [ 63 ]. As such, this reality likely prevents many Americans with lower incomes who face disproportionate access barriers [ 64 ] from purchasing FVs.…”
Section: Special Issue Contributions To Advancing Nutrition Security ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Arce et al (2021) found that the acceptability of some FVs is reported to have a high influence on consumption. In this sense, price as an FV consumption barrier is likely to be hiding other determinants (Livingstone et al, 2020;Hohoff et al, 2022;Young and Stewart, 2022). Of course, price is relevant in many consumption decisions; however, in some cases, it is likely to have overstated their actual effect on consumption.…”
Section: Discussionmentioning
confidence: 99%